INFLUENCE OF KINETIC VARIABLES DURING THE PROPULSION IN THE LONG JUMP OF CHILDREN IN DEVELOPMENT (Fiep Bulletin - online, 2011)
The propose of this study was to analyze the influence of kinetic characteristics for the stand long jump of children in the development. We used a AMTI`s force platform with a frequency of 900 Hz for the acquisition of the jump in the propulsion phase. We analyzed 33 children, age between 5 and 12 years old, of both sexes, were analyzed 3 attempts each. The results indicate that during the preparation of long jump the most important variables in performance is the total horizontal impulse and peak horizontal force, and that the variable that affected negatively the jump was the vertical impulse. Thus we can conclude that specifies using a preparation towards the kinetics of the jump may result in better performance in the long jump, which facilitates the process of teaching and learning.
Keywords: stand long jump; children; biomechanics